2016
DOI: 10.1242/jcs.178434
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the PI3K–Akt and mTORC1 signaling pathways promotes the elongation of vascular endothelial cells

Abstract: Endothelial cell morphology needs to be properly regulated during angiogenesis. Vascular endothelial growth factor (VEGF) induces endothelial cell elongation, which promotes sprouting of pre-existing vessels. However, therapeutic angiogenesis using VEGF has been hampered by side effects such as elevated vascular permeability. Here, we attempted to induce endothelial cell elongation without an overdose of VEGF. By screening a library of chemical inhibitors, we identified phosphatidylinositol 3-kinase (PI3K)-Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 75 publications
3
37
0
Order By: Relevance
“…PI3K signalling is activated by various growth factors, including VEGF43. Our data show that VEGF signalling is increased in ALK1 mutant cells.…”
Section: Discussionmentioning
confidence: 60%
“…PI3K signalling is activated by various growth factors, including VEGF43. Our data show that VEGF signalling is increased in ALK1 mutant cells.…”
Section: Discussionmentioning
confidence: 60%
“…Importantly, VE-cadherin expression remains constant during cell growth (Lampugnani et al, 1995; and after treatment with the proangiogenic growth factor VEGF or the γ-secretase inhibitor DAPT, which also induces angiogenesis (Cao et al, 2017). These treatments all cause a change in cell shape from polygonal to elongated cells (Tsuji-Tamura and Ogawa, 2016;Cao et al, 2017). This results in an increased length of cell junctions, which dilutes the given amount of VE-cadherin along the junctions accordingly.…”
Section: Relationship Between Cell Shape Junction Dynamics and Migramentioning
confidence: 99%
“…Indeed, cell elongation occurs in angiogenesis in vivo in the mouse retina and in zebrafish, and can also be induced in vitro by pro-angiogenic factors, such as VEGF and the γ-secretase inhibitor DAPT (Sauteur et al, 2014; Tsuji-Tamura and Ogawa, 2016; Cao et al, 2017;Paatero et al, 2018). The signals underlying cell elongation involve the loss of tension and microtubule polarization, as well as Rac, PI3K, Foxo1 and mTOR signaling (Furuyama et al, 2004;Tsuji-Tamura and Ogawa, 2016;Cao et al, 2017). The loss of tension accompanies the formation of invaginations, which might increase the cell junction length; this, in turn, decreases Rel-VEcad-C, inducing JAIL formation and thus affects local cell junction dynamics (see above), which is required for the initiation of cell elongation.…”
Section: Significance Of Jail Formation In Cell Sheet Migration and Amentioning
confidence: 99%
“…Previous studies revealed that PI3K‐mediated signaling in mast cells can regulate vascular leakage in asthma . The histamine released from mast cells resulted in the disruption of endothelial cell function via PI3K/Akt signaling pathway . PI3K signaling was also involved in sphingosine‐1‐phosphate receptor‐2 (S1PR2)‐mediated paracellular permeability increases by opening adherens junctions between the neighboring endothelial cells .…”
Section: Introductionmentioning
confidence: 99%